Spatialities of Family and Care in Contexts of (In)Securitized Migration: The Case of Hindered Parenting among Seasonal Workers in Switzerland - Victor Santos Rodriguez (GéoProximitéS)
This article explores the effects of the (in)securitization of migration on family and care. It mobilizes proximity as a “fertile heuristic” to shed light on the issue of hindered parenting in the context of Switzerland in the second half of the 20th century, where a strict ban on family reunification targeted foreign workers.